A study on maintenance management for water supply in high rise building / Mohd Saifulnizam Abdul Wahab - Abdul Wahab, Mohd Saifulnizam (2008)
According to the development of the urban area, include the skyscrapers building, which are proven that our country is still in development. However there are several problems that need to be solved. This problem is likely minor but it will increase to the major if not be barricade. The problems that occurred are lack of water supply or lack of water pressure to supply the water to the consumer. For example, almost every month we heard about the water problems. The main cause of the problem is the lack of important data to determine the rate of water that used by the consumer daily. All the problem among this water data will be get from full research about how the use of water in our life. In this research, it will focus on the maintenance management for high rise building. As we know, the maintenance management is very important for the water supply system. The material and equipments should be inspected to determine whether its follow the specification or not. The research will generally analyze about types of maintenance program that used for the high rise building. In addition, research will also focus on the cause of why the sources of water loose. Such as the leaking on the jointing pipe, leaking on the supply tank or others. The most important on water supply system for high rise building Is because of the pressure and the equipment for the water supply system.